Considerations and practice of establishment of a specialized Traditional Chinese Medicine nursing outpatient service model (专科中医护理门诊服务模式建设的思考与实践) - LIANG Qiuhui (梁秋会); CAO Yanxia (曹艳霞); WANG Xiujun (王秀均); WANG Jing (王敬); JI Yingxia (季英霞); WANG Jingyun (王静云); CHEN Yixiu (陈一秀); LI Shuo (李硕) (Association of Integrative Nursing, 2022)
This paper explored the establishment practice of a specialized Traditional Chinese Medicine(TCM) nursing outpatient service model, and summarize the characteristics of advanced practical service in TCM nursing outpatient service. By establishing the role of TCM nursing outpatient nurses, clarifying the characteristics of nursing practice activities dominated by nurse specialists of TCM nursing treatment, forming an integrated service model of specialized medical care, strengthening the quality management of TCM nursing outpatient services, and doing a good job in training and assessment of outpatient nurses' core competencies, great efforts have been made to continuously enrich the connotation of quality nursing services with TCM nursing characteristics, accelerate the establishment of TCM nursing service system, and promote the process of nursing specialization, which plays a positive role in promoting the long-term sustainable development of TCM nursing specialties, and is worthy of being performed exploration and practice by nursing managers and clinical nursing staff with specialty work experience. (本文探讨了专科中医护理门诊服务模式的建设, 总结中医护理门诊高级实践服务特点。通过确立中医护理门诊护士的角色作用, 明确中医护理治疗专科护士主导下的护理实践活动的特点, 形成专科医护一体化服务模式, 加强中医护理门诊服务质量管理, 做好出诊护士核心能力培训考核等, 不断丰富中医护理特色的优质护理服务内涵, 加快中医护理服务体系的建立, 促进护理专科化进程, 对中医护理专科的长期可持续发展有着积极的推动作用, 值得广大护理管理者和具备专科工作经验的临床护理人员去开拓和实践。)